Uncovering CLIL (Content and Language Integrated Learning) in bilingual and multilingual education - Mehisto, Peter; Marsh, David (Oxford Macmillan, 2008)
This book is a practical and informative handbook which will be of use to teachers of all levels of experience. It examines language and content teaching, and reveals how the two can go hand in hand, giving examples of how to use CLIL at primary , secondary and vocational levels.
Contents.
Keywords: Learning; Teaching; Classroom Techniques; Grammar; English - foreign language; Methodology